Agent-based Big Data Analytics in retailing: A case study - Ahmed F.D.; Jaber A.N.; Majid M.B.A.; Ahmad M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Autonomous agents; Complex networks; Computer software; Consumer behavior; Data handling; Data mining; Decision making; Digital storage; Intelligent agents; Metadata; Multi agent systems; Software engineering; Business transaction; Complex structure; Data analytics; Hidden patterns; Industrial automation; Massive data sets; Pattern visualization; Retail; Big data